Electroplated component and method for manufacturing same

By reasonably preparing chromium, carbon and oxygen in the electroplating film and controlling its composition and hardness, the problem of easy destruction of the 3V chromium bath precipitation electroplating film during grinding is solved, and efficient wear resistance and environmental protection are achieved.

CN119836493APending Publication Date: 2025-04-15ASTEMO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380063526.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-07
Filing Date
2023-09-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During grinding, the 3V chromium bath precipitation electroplating film formed in the sliding member is prone to brittle damage (leaving damage).

Method used

By containing chromium, carbon and oxygen in the electroplating film, the content of chromium is ensured to be between 60 and 80 at%, the content of carbon is between 16.5 and 30 at%, and the press-in hardness of the outer surface reaches more than 7 GPa, and the crystallization degree is controlled to be less than 4% to improve the wear resistance of the electroplating film.

Benefits of technology

It achieves the effect of difficult peeling damage during grinding, and does not cause problems in environmental nature compared with 6-valent chromium, providing an efficient solution to replace 6-valent chromium electroplating film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119836493A_ABST
    Figure CN119836493A_ABST
Patent Text Reader

Abstract

The plated member has, on the outer surface thereof, a plating film containing at least chromium, carbon, and oxygen and having chromium precipitated by a trivalent chromium bath as the main component, the plating film containing 60-80 at% of chromium and 16.5-30 at% of carbon, the press-in hardness of the outer surface being 7 GPa or more, the peak integrated intensity ratio of the measured value as measured by X-ray diffraction and the degree of crystallization as calculated according to formula (1) being 4% or less, and the thickness of the plating film being 0.5-5 [mu] m. Degree of crystallization (peak integral intensity ratio) = {(crystallinity) / (crystallinity + amorphous)} * 100% (1) where the indentation hardness represents a value measured by instrumented indentation hardness by nanoindentation, and the integral intensity ratio of formula (1) represents a value determined by XRD analysis at 2 [theta]: 30-60 degrees, the half-value width of crystallinity: < 3, and the half-value width of amorphous: > = 3.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to electroplated parts and methods of making the same.

[0002] This application claims priority based on Japanese Patent Application No. 2022-142218 filed in Japan on September 7, 2022, the contents of which are incorporated herein by reference. Background Art

[0003] Patent Document 1 describes a technique in which a chromium electroplated layer deposited in a trivalent chromium bath, which has no toxicity or pollution problems with respect to hexavalent chromium, is used for a plate-making roller.

[0004] Prior Art Literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2008-143169 Summary of the invention

[0007] Technical problem to be solved by the invention

[0008] Among chromium plating films formed on rods that come into sliding contact with sliding parts, plating films deposited using a trivalent chromium bath have attracted attention as an alternative to plating films deposited using a hexavalent chromium bath.

[0009] However, according to the research conducted by the present inventors, when a rod having a plated film deposited by a conventional trivalent chromium bath is polished, brittle failure (peeling failure) of the plated film occurs.

[0010] An object of the present invention is to provide a plated component such as a rod having a plated film deposited in a trivalent chromium bath that is less likely to be delaminated during polishing, and a method for producing the same.

[0011] Means for solving problems

[0012] The electroplated component of the present invention has an electroplated film on the outer surface which contains at least chromium, carbon and oxygen and has chromium precipitated from a trivalent chromium bath as a main component, wherein the electroplated film contains chromium: 60 to 80 at%, carbon: 16.5 to 30 at%, and the indentation hardness of the outer surface is 7 GPa or more.

[0013] The peak integrated intensity ratio of the measured value of the X-ray diffraction measurement and the crystallinity calculated by the following formula (1) is 4% or less,

[0014] Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1)

[0015] The indentation hardness is a value obtained by measuring the instrumented indentation hardness using the nanoindentation method (ISO 14577). The integrated intensity ratio of formula (1) is a value obtained by XRD (X-ray diffraction) analysis with 2θ: 30-60°, half-value width of crystalline: <3, and half-value width of amorphous: ≥3.

[0016] Effects of the Invention

[0017] According to the present invention, it is possible to provide a plated component having a chromium plated film mainly composed of chromium precipitated from a trivalent chromium bath, which is less environmentally friendly than hexavalent chromium and which is less likely to be peeled off and damaged during polishing. In addition, it is possible to provide a technology for manufacturing the plated component. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a cross-sectional view showing the overall structure of a shock absorber including a piston rod as a first embodiment of a plated component according to the present invention.

[0019] Figure 2 This is a front view showing a rough shape of the piston rod.

[0020] Figure 3 is a diagram showing the upper structure of the shock absorber. Figure 1 An enlarged partial cross-sectional view of section A.

[0021] Figure 4 is a diagram showing the structure of the front end portion of the piston rod. Figure 1 An enlarged partial cross-sectional view of part B.

[0022] Figure 5 This is a flow chart showing an example of the manufacturing process of the piston rod.

[0023] Figure 6 This is a perspective view of the main parts showing an example of a grinding device used for grinding the outer diameter of the piston rod.

[0024] Figure 7 This is a graph showing the relationship between the precipitation rate and the degree of crystallinity of the plated films formed in Examples.

[0025] Fig. 8A This is a graph showing the relationship between the deposition rate and the carbon concentration of the electroplated film formed in the example.

[0026] Figure 8B This is a graph showing the relationship between the deposition rate and oxygen concentration of the plated film formed in Examples.

[0027] Figure 8C This is a graph showing the relationship between the deposition rate and the chromium concentration of the electroplated film formed in Examples.

[0028] Fig. 9 This is a table showing the physical property values ​​of the plated films formed in Examples.

[0029] Fig.10 The polishing marks of the brittle mode formed on the plating film of the comparative example sample are shown. (A) is a photograph enlarged by 500 times, and (B) is a photograph enlarged by 5000 times.

[0030] Fig.11 The polishing marks show the ductility mode of the plated film formed on the sample of the example. (A) is a photograph enlarged by 500 times, and (B) is a photograph enlarged by 5000 times.

[0031] Fig.12 This is a graph showing the relationship between the coating hardness and the number of polishing marks having a width of 8 μm or more for samples of the examples and samples of the comparative examples.

[0032] Fig.13 This is a graph showing the relationship between the amount of carbon coating and the number of polishing marks having a width of 8 μm or more for samples of the examples and the comparative examples.

[0033] Fig.14 This is a graph showing the relationship between the coating hardness and the coating carbon content of the samples of the examples and the samples of the comparative examples.

[0034] Fig.15 (A) shows the analysis results of X-ray diffraction of the comparative example sample, and (B) is a surface photograph showing the polishing marks of the sample.

[0035] Fig.16 (A) shows the analysis results of the X-ray diffraction of the sample of the example, and (B) is a surface photograph showing the polishing marks of the sample.

[0036] Fig.17 This is a graph showing the relationship between the deposition rate (film formation rate) of the electroplated film formed in Examples and the size of the oriented chromium crystal grains.

[0037] Fig.18 This is a diagram showing a TEM image of a cross section of a coating in a ductile mode in Example 2 of the bath seed A1.

[0038] Fig.19 (A) is a diagram showing a TEM image of a cross section of a coating in a brittle mode for Comparative Example 1 of the bath seed A1, and (B) is a diagram showing a TEM image of a cross section of a coating in a brittle mode for Comparative Example 4 of the bath seed A1.

[0039] Fig. 20 This is a diagram showing a TEM image of a cross section of a coating in a ductile mode in Example 5 of the bath seed A2.

[0040] Fig.21 (A) is a diagram showing a TEM image of a cross section of a coating in a brittle mode for Comparative Example 9 of the bath seed A2, and (B) is a diagram showing a TEM image of a cross section of a coating in a brittle mode for Comparative Example 12 of the bath seed A2.

[0041] Fig. 22 This is a diagram showing an electron diffraction pattern of a film cross section in a ductile mode in Example 2 of the bath seed A1.

[0042] Fig.23 (A) is a diagram showing an electron diffraction pattern of a coating cross section in a brittle mode for Comparative Example 1 of the bath seed A1, and (B) is a diagram showing an electron diffraction pattern of a coating cross section in a brittle mode for Comparative Example 4 of the bath seed A1.

[0043] Fig.24 This is a diagram showing an electron diffraction pattern of a film cross section in a ductile mode in Example 5 of the bath seed A2.

[0044] Fig.25 (A) is a diagram showing an electron diffraction pattern of a coating cross section in a brittle mode for Comparative Example 9 of the bath seed A2, and (B) is a diagram showing an electron diffraction pattern of a coating cross section in a brittle mode for Comparative Example 12 of the bath seed A2. DETAILED DESCRIPTION

[0045] Hereinafter, a shock absorber (cylinder device) including a piston rod as one embodiment of the plated component of the present invention will be described.

[0046] It should be noted that the embodiments described below are specifically described for better understanding of the gist of the invention, and do not limit the present invention unless otherwise specified. In addition, the drawings used in the description of the embodiments shown below are appropriately scaled to make it easier to see each part.

[0047] Figure 1 It is a partial cross-sectional view showing the overall structure of a shock absorber (cylinder device) 1 including a piston rod 21 as an example of a plated component of the present invention.

[0048] A plating film described later is formed on the outer peripheral surface of the piston rod 21 . Before describing the plating film, the overall structure of the shock absorber 1 will be described.

[0049] "Cylinder device"

[0050] Figure 1The cylinder device 1 shown is a shock absorber for a suspension device of an automobile or a railway vehicle, and more specifically, a strut-type suspension device of an automobile. The cylinder device 1 comprises: a cylindrical inner cylinder (cylinder) 2 in which a working fluid is sealed, and an outer cylinder 3 having a larger diameter than the inner cylinder 2 and disposed on the outer circumference of the inner cylinder 2, with a bottomed cylindrical outer cylinder 3 in which a working fluid and a working gas are sealed to form a storage chamber R between the inner cylinder 2. The cylinder device 1 is a double-cylinder shock absorber in which the inner cylinder 2 is disposed in the outer cylinder 3. Figure 1 CL in the figure represents the center line of the inner tube 2 and the outer tube 3 .

[0051] The outer tube 3 has a cylindrical side wall portion 7 and a bottom 8 that blocks one axial end side of the side wall portion 7. The inner tube 2 is cylindrical. The inner tube 2 is engaged with the bottom 8 of the outer tube 3 via an annular base valve 13 installed at one axial end thereof. The inner tube 2 is engaged with the other axial end side of the side wall portion 7 via an annular rod guide portion 11 installed at the other axial end thereof.

[0052] The base valve 13 is disposed coaxially with the outer tube 3 , and the stem guide 11 is fitted with the inner tube 2 and the outer tube 3 to support the other end of the inner tube 2 coaxially with the outer tube 3 .

[0053] An oil seal 15 is disposed on the rod guide portion 11 on the side opposite to the bottom portion 8. A locking portion 16 bent inward is formed on the other axial end of the side wall portion 7, and the oil seal 15 is supported by the locking portion 16.

[0054] A piston 25 is slidably fitted in the inner tube 2. The piston 25 divides the inner tube 2 into a first chamber 22 and a second chamber 23. The first chamber 22 is formed between the piston 25 and the rod guide 11, and the second chamber 23 is formed between the piston 25 and the base valve 13. The second chamber 23 is divided from the storage chamber R by the base valve 13 provided on one end side of the inner tube 2.

[0055] The metal piston rod 21 is connected to the piston 25 by a nut 26. The piston rod 21 has a cylindrical large diameter portion 21a, and protrudes to the outside from one end side of the inner tube 2 and the outer tube 3 through the rod guide 11 and the oil seal 15. The large diameter portion 21a of the piston rod 21 is inserted into the inner side of the rod guide 11 and the inner side of the oil seal 15 so as to be slidable.

[0056] A small diameter portion 21 b is formed at the front end side of the piston rod 21 , and the piston 25 is inserted through the small diameter portion 21 b . The piston 25 is attached to the piston rod 21 by screwing a nut 26 into a threaded portion at the front end of the small diameter portion.

[0057] An annular groove 21c is formed in the large diameter portion 21a of the piston rod 21 near the small diameter portion 21b, and an annular inner stopper 24 is mounted to engage with the annular groove 21c. An annular rebound rubber 19 is disposed on the inner stopper 24.

[0058] like Figure 2 As shown, in the large diameter portion 21a of the piston rod 21, a portion between a position P1 separated from the annular groove 21c and a connection portion P2 connected to a bolt portion 21d as a mounting portion to the vehicle body constitutes a sliding range A.

[0059] An electroplated film mainly composed of chromium deposited by a trivalent chromium bath described in detail later is formed on the outer peripheral surface including the sliding range A of the piston rod 21 .

[0060] The piston rod 21 moves axially together with the piston 25. The oil seal 15 through which the large diameter portion 21a of the piston rod 21 is inserted seals the inner tube 2 and the outer tube 3 with the piston rod 21 to prevent the working fluid in the inner tube 2, the working gas in the storage chamber R, and the working fluid from leaking to the outside.

[0061] like Figure 4 As shown, passages 27 and 28 penetrating in the axial direction are formed in the piston 25 . Figure 1 The passages 27 and 28 shown can communicate with the first chamber 22 and the second chamber 23. The piston 25 is provided with an annular disk valve 28a that can block the passage 28 by abutting against the upper surface of the piston 25. The piston 25 is provided with an annular disk valve 27a that can block the passage 27 by abutting against the lower surface of the piston 25.

[0062] The piston rod 21 moves to the shortening side ( Figure 1 When the piston 25 moves in the direction of narrowing the second chamber 23, the piston 25 moves in the direction of narrowing the second chamber 23. When the pressure of the second chamber 23 becomes higher than the pressure of the first chamber 22 by a predetermined value or more, the disk valve 28a opens the passage 28, and at this time, a damping force is generated.

[0063] The piston rod 21 moves to the extension side where the amount of protrusion from the inner tube 2 and the outer tube 3 increases toward the upper end side ( Figure 1 When the pressure in the first chamber 22 rises, the piston 25 moves in the direction of shortening the first chamber 22. As a result, when the pressure in the first chamber 22 is higher than the pressure in the second chamber 23 by a predetermined value or more, the disk valve 27a opens the passage 27, and a damping force is generated at this time.

[0064] like Figure 1 As shown, passages 29, 29 penetrating the base valve 13 in the axial direction are formed in the base valve 13. The passage 29 can communicate with the second chamber 23 and the storage chamber R. An annular disk valve 30 is arranged on the bottom surface side of the base valve 13 so as to block one passage 29 by abutting against the bottom surface side of the base valve 13. An annular disk valve 31 is arranged on the upper surface side of the base valve 13 so as to block the other passage 29 by abutting against the upper surface side of the base valve 13.

[0065] The disk valve 30 is a check valve that allows the working fluid to flow from the second chamber 23 to the reservoir chamber R through the passage 29 on one side, and restricts the working fluid from flowing in the opposite direction through the passage 29. The disk valve 30 is a valve that opens the passage 29 when the piston rod 21 moves toward the shortening side and the pressure in the second chamber 23 becomes higher than the pressure in the reservoir chamber R by a predetermined value or more.

[0066] The disk valve 31 is a check valve that allows the working fluid to flow from the reservoir chamber R to the second chamber 23 through the other passage 29, and restricts the working fluid from flowing in the opposite direction through the passage 29. The disk valve 31 is a valve that opens the passage 29 when the piston rod 21 moves to the extension side and the pressure of the second chamber 23 becomes lower than the pressure of the reservoir chamber R by a predetermined value or more.

[0067] like Figure 1 As shown, a mounting lug 33 is mounted on the outer side of the bottom portion 8. The cylinder device 1 is used by mounting the outer side portion of the piston rod 21 and the mounting lug 33 between relatively moving members as mounting objects.

[0068] The cylinder device 1 is used by, for example, connecting the outer end of the piston rod 21 to the body side of a vehicle and connecting the mounting eye 33 to the wheel side of the vehicle.

[0069] In the cylinder device 1, the piston rod 21 and the piston 25 are integrally slid in the inner tube 2 to change the volume of the first chamber 22 and the second chamber 23. At this time, the flow resistance of the liquid acting on the piston 25 and the base valve 13 can generate a damping force.

[0070] like Figure 3 As shown, the rod guide 11 is substantially stepped annular, with a large diameter portion 11a formed on one axial side and a small diameter portion formed on the other side. The large diameter portion 11a fits with the inner circumference of the outer tube 3, and the small diameter portion fits with the inner circumference of the inner tube 2.

[0071] An annular protrusion 11c protruding in the axial direction is formed at the end of the large diameter portion 11a of the rod guide 11, and a connecting hole 11d is formed corresponding to a portion of the annular protrusion 11c so as to allow the rod guide 11 to pass through in the axial direction. In the connecting hole 11d, the side of the rod guide 11 opposite to the annular protrusion side in the axial direction is open to the storage chamber R.

[0072] The oil seal 15 includes a sealing member body 37 which is an integrally formed product in which a metal annular member 36 is embedded in a sealing member 35 made of synthetic rubber, and a metal annular spring 38. The annular member 36 maintains the shape of the sealing member 35 and gives the sealing member body 37 a strength for fixing to a target part. The sealing member body 37 is mounted on the end side of the outer tube 3 by sandwiching the annular member 36 between the locking portion 16 and the annular convex portion 11c.

[0073] The sealing member 35 includes a dustproof lip portion 35 a , an oil seal lip portion 35 b , a seal ring portion 35 c , and a check lip portion 35 d , and surrounds the periphery of the piston rod 21 to perform a sealing function.

[0074] The cylinder device 1 is configured such that the piston rod 21 or the outer cylinder 3 is repeatedly subjected to external impact force along its axial direction when the vehicle is traveling. Whenever the impact force is applied, the piston rod 21 moves toward the shortening side or the extending side, and a damping force acts at this time. In this way, the cylinder device 1 functions as a buffer for the strut suspension of the automobile.

[0075] In addition, the outer peripheral surface of the piston rod 21 is provided with a plating film deposited by a trivalent chromium bath as described below. This plating film is a plating film that is less likely to cause brittle failure (peeling failure) when the outer peripheral surface of the piston rod 21 is polished to the target surface roughness by outer diameter grinding during the manufacture of the piston rod 21. When the outer peripheral surface is finished to the polished surface with the target surface roughness and the piston rod 21 is provided with the plating film described in detail later, the large diameter portion 21a of the piston rod 21 repeatedly slides relative to the sealing member 35, which can produce excellent sliding characteristics and obtain excellent wear resistance.

[0076] Figure 5 This is a flowchart showing an example of a manufacturing process of the piston rod 21 .

[0077] like Figure 5 As shown in step S1 , in order to form the piston rod 21 , a rod material such as a steel bar made of a desired type of steel material is prepared.

[0078] The rod material is subjected to heat treatment such as high-frequency quenching and tempering in step S2, and is subjected to surface hardening treatment suitable for a piston rod.

[0079] Next, if Figures 1 to 4 As shown in the schematic form, cutting is performed in step S3, and outer diameter grinding is performed in step S4.

[0080] Next, relative to Figures 1 to 4 The piston rod of the general shape shown in the figure is subjected to base electroplating treatment such as nickel electroplating in step S5, and then subjected to chromium electroplating treatment mainly based on chromium precipitated by a trivalent chromium bath in step S6. It should be noted that in step S5 of base electroplating treatment, other base electroplating treatment may be performed instead of nickel electroplating, or step S5 of base electroplating treatment may be omitted, or base electroplating may be omitted.

[0081] Next, in step S7 , the outer diameter of the piston rod is ground, and the piston rod having the final surface shape can be obtained by precision finishing.

[0082] The present embodiment is characterized by the electroplating treatment performed in step S6 and the chromium electroplating film mainly composed of chromium deposited from a trivalent chromium bath formed on the piston rod.

[0083] The chromium electroplating film deposited in the trivalent chromium bath used in the present embodiment contains chromium as a main component and contains one or more impurity elements selected from carbon (C) and oxygen (O) as other elements.

[0084] For example, the chromium plating film preferably contains 60 to 80 at % of chromium and 16.5 to 30 at % of carbon, and has a surface indentation hardness of 7 GPa or more.

[0085] The indentation hardness refers to a value measured by instrumented indentation hardness using a nanoindentation method (ISO 14577). For example, an indentation weight of 20 mN may be used.

[0086] The chromium electroplated film may contain oxygen in an amount of about 2 to 6 at % among the above elements. Furthermore, in addition to the above elements, the chromium electroplated film may contain either chlorine (Cl) or iron (Fe) in an amount of about 5 at % or less as an impurity element.

[0087] In addition, the carbon content is more preferably about 18 to 25 at %, and the oxygen content is more preferably about 2 to 5 at %.

[0088] The main component of the electroplated film is chromium, which is preferably contained as much as possible. As described later, the carbon contained in the electroplated film is derived from the organic components that constitute the electroplating bath. When the carbon content is less than 16.5 at%, the possibility of peeling marks in the brittle mode during outer diameter grinding increases. According to the upper limit of the concentration of the organic salt added to the electroplating bath, the maximum carbon content that the electroplated film can contain is 30 at%.

[0089] The oxygen content of the plated film is in the range of 2 to 6 at%.

[0090] When the oxygen content is less than 2 at %, there is a problem that the possibility of generating peeling marks in the brittle mode increases. When the oxygen content exceeds 6 at %, there is a problem that the possibility of generating peeling marks in the brittle mode increases as described above.

[0091] In the electroplated film of the present embodiment, elemental analysis can be performed by an electron probe micro analyzer (EPMA), and for example, conditions such as an acceleration voltage of 10 kV and an irradiation current of 100 nA can be employed.

[0092] It should be noted that in the specification of the present application, when a numerical range is specified, when the upper limit and the lower limit are indicated by "~", unless otherwise specified, the concept of including the upper limit and the lower limit is included. Therefore, the 60-80 at% represents a range of 60 at% or more and 80 at% or less.

[0093] The impurity elements other than chromium are presumably derived from organic components such as carboxylate, pH buffer, and conductivity salt described below contained in the electroplating bath.

[0094] In the chromium electroplated film of the present embodiment, the content of impurities contained in the electroplated film varies depending on the electroplating treatment conditions, and is related to the current density, bath temperature, and pH conditions.

[0095] This is presumably because the availability of additives during chromium precipitation is affected by current density (reduction rate), bath temperature (reduction rate), and pH (complex formation, reduction rate).

[0096] [Film structure of hard trivalent chromium plating film by TEM analysis]

[0097] The structure of the electroplated film of this embodiment is preferably that the diameter of the oriented chromium crystal particles is less than 10 nm, and the substrate has no oriented microcrystals. In addition, in the electron diffraction pattern, it is preferred that there is no chromium diffraction spot at a position where the interplanar distance d value is 2.0 to 2.2 Å (chromium d value: 2.04 Å).

[0098] The structure of the electroplated film varies depending on the electroplating treatment conditions, and it can be confirmed in the examples described below that it is particularly susceptible to the influence of current density, bath temperature, and pH conditions. It is speculated that the reason is that the incorporation of additives during chromium precipitation is affected by current density (reduction rate), bath temperature (reduction rate), and pH (complex formation).

[0099] The structure of the plating film of the present embodiment can be observed using a transmission electron microscope (STEM), and conditions such as an acceleration voltage of 200 kV can be selected.

[0100] When obtaining an electron diffraction pattern, the measurement conditions can be an acceleration voltage of 200 kV, a wavelength λ of the electron beam at 200 kV of 0.00251 nm, and a camera length of 399.4 mm.

[0101] In the present embodiment, the plating bath used for the chromium plating treatment may contain a trivalent chromium salt and various components such as a complexing agent, a pH buffer, and a conductivity salt as additives.

[0102] As the trivalent chromium salt, chromium chloride, chromium sulfate, basic chromium sulfate, etc. can be used, and among these, chromium chloride is preferably used.

[0103] As the complexing agent, glycine, formic acid, oxalic acid, acetic acid, and the like, which are carboxylates, can be used. Among these, glycine is preferably used.

[0104] As the pH buffer, boric acid, citric acid, and the like can be used, and among these, boric acid is preferably used.

[0105] As the conductivity salt, ammonium chloride, ammonium sulfate, ammonium sulfonate, and the like can be used, and among these, ammonium chloride is preferably used.

[0106] When a strongly acidic trivalent chromium bath is used as the electroplating bath, a strongly acidic bath weaker than pH 0.1 is preferred, for example, a strongly acidic bath in the range of pH 0.1 to pH 0.6 is preferred, and a strongly acidic bath in the range of pH 0.2 to pH 0.5 is more preferred.

[0107] When the pH is strongly acidic below pH 0.1, it is difficult to obtain an electroplated film mainly composed of chromium precipitated from a trivalent chromium bath, which is the purpose of the present application. When the pH is higher than pH 0.6, the glossiness of the electroplated film deteriorates, and the absorption of impurity elements during the precipitation of chromium changes due to the film formation rate. Therefore, it is impossible to obtain an electroplated film mainly composed of chromium precipitated from a trivalent chromium bath, which is the purpose of the present application.

[0108] When a weakly acidic trivalent chromium bath is used as the electroplating bath, blue chromium (trade name of Atotech) can be used as an example of a commercially available product. When blue chromium is used, as an example, a pH range of 5.2 to 5.8 can be selected. The pH is more preferably in the range of 5.4 to 5.6.

[0109] In the present embodiment, when trivalent chromium plating solution blue chrome manufactured by Atotech is used, the plating bath used in the chromium plating treatment can be a plating bath containing trivalent chromium salt and various components such as a complexing agent, a pH buffer, and a conductivity salt as additives.

[0110] As the trivalent chromium salt, chromium chloride, chromium sulfate, basic chromium sulfate, etc. can be used, and among these, chromium sulfate is preferably used.

[0111] As the complexing agent, glycine, formic acid, oxalic acid, acetic acid, and the like, which are carboxylates, can be used. Among these, formic acid is preferably used.

[0112] As the pH buffer, ammonia, boric acid, citric acid, etc. can be used, and among these, ammonia is preferably used.

[0113] As the conductivity salt, ammonium chloride, ammonium sulfate, ammonium sulfonate, and the like can be used, and among these, ammonium sulfate is preferably used.

[0114] The pH of the plating bath is preferably acidic, preferably weaker than pH 6.0, for example, within the range of pH 5.3 to pH 5.7.

[0115] In an acidic environment of pH 5.3 or less, an electroplated film mainly composed of chromium deposited in a trivalent chromium bath, which is the purpose of the present invention, cannot be obtained. In an acidic environment of pH 5.7 or lower, an electroplated film mainly composed of chromium deposited in a trivalent chromium bath, which is the purpose of the present invention, cannot be obtained because of the deterioration of the glossiness of the electroplated film and the change in the incorporation of impurity elements during chromium deposition due to the film formation rate.

[0116] When the current density during electroplating is high, the film forming speed is fast and the productivity is high. In order to achieve the above composition, the current density can be selected: 45~100A / dm 2 Under the conditions of high current density and high concentration of trivalent chromium salt, the film forming speed is fast, but the size of the film forming speed causes the availability of impurity elements during chromium precipitation to change. In order to obtain the above-mentioned desired chromium content and carbon content in the obtained electroplated film, it is desirable to have a preferred film forming speed.

[0117] It should be noted that the plating bath temperature is preferably high, and can be selected within the range of 55 to 80° C., for example.

[0118] The plating bath is preferably stirred by a slow stirring method such as flowing the plating solution near the surface to be plated. As the anode material, Pt, Ti, Ir, graphite, etc., which are highly insoluble, can be used.

[0119] When the current density during electroplating is high, the film forming speed is fast and the productivity is high. In order to achieve the above composition, the current density can be selected: 45~100A / dm 2 The film forming speed is fast under the conditions of high current density and high concentration of trivalent chromium salt, but the film forming speed changes the availability of impurity elements when chromium is precipitated. In order to achieve the above-mentioned desired chromium content and carbon content in the obtained electroplated film, it is desirable to have a preferred film forming speed.

[0120] It should be noted that the plating bath temperature is preferably high, and can be selected within the range of 55 to 80° C., for example.

[0121] The plating bath is preferably stirred by a slow stirring method such as flowing the plating solution near the surface to be plated. As the anode material, Pt, Ti, Ir, graphite, etc., which are highly insoluble, can be used.

[0122] The electroplated film formed by the trivalent chromium bath precipitated by the electroplating treatment has an amorphous structure when the film is formed. The electroplated film with the amorphous structure can also be a non-crystalline electroplated film that is heat treated at a heating temperature below 200°C and has a crystallinity of, for example, 4% or less, preferably 2% or less, and more preferably 1% or less.

[0123] The degree of crystallinity is a value calculated from the peak integrated intensity ratio of the values ​​measured by X-ray diffraction measurement and the following formula (1).

[0124] Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1)

[0125] The integrated intensity ratio in formula (1) indicates a value obtained in XRD (X-ray diffraction) analysis with 2θ: 30 to 60°, half value width of crystalline: <3, and half value width of amorphous: ≥3.

[0126] In this specification, a plated film having a crystallinity of 0% obtained by the following formula (1) is considered to be amorphous, and a plated film having a crystallinity of 4% or less is a concept including a plated film having a crystallinity of 0%.

[0127] The electroplated film of this embodiment is preferably less likely to produce grinding marks due to the brittle mode when subjected to grinding processing. Figure 6 Polishing marks produced when polishing is performed using the film polishing apparatus shown.

[0128] Figure 6 The film polishing device 40 shown has driving rollers 41 and 42, which are arranged close to each other so as to be freely rotatable around the horizontal axis when a part of the circumferential surface of each other is brought close to each other, and a rod raw material 21A for a piston rod for processing purposes can be placed on the boundary between these close driving rollers 41 and 42.

[0129] When the rod material 21A is arranged on the boundary portion between the driving rollers 41 and 42 that are arranged closely, the supported rod material 21A can be rotated about the axis along with the rotation of the driving rollers 41 and 42 .

[0130] A back pressure roller 43 is horizontally arranged above the rod material 21A at the boundary between the driving rollers 41 and 42 so as to be rotatable in the circumferential direction. A polishing film 44 can be supplied to the bottom surface of the back pressure roller 43 from a film supply device (not shown).

[0131] The polishing film 44 is a strip-shaped film, and the polishing film 44 can be supplied to the bottom surface side of the back pressure roller 43 from a film supply device (not shown) provided on one side in a direction perpendicular to the central axis of the back pressure roller 43 as indicated by arrow a. In addition, the film 44 can be moved and wound to a film winding device (not shown) provided on the other side in a direction perpendicular to the central axis of the back pressure roller 43 as indicated by arrow b. The polishing film 44 is wound on the film supply device of a necessary length, and can be continuously supplied to the bottom surface side of the back pressure roller 43.

[0132] The back pressure roller 43 is supported to be rotatable while being maintained in a horizontal state by an up-down moving mechanism (not shown), but is supported so that its up-down position can be finely adjusted by the up-down moving mechanism. A pressure head 45 supported by an up-down front-back moving mechanism (not shown) is provided above the back pressure roller 43. The pressure head 45 can be lowered from slightly above the back pressure roller 43 as shown by arrow c, while pressing the back pressure roller 43 downward with a prescribed pressure. In addition, the pressure head 45 is supported so that it can move freely along the axial direction of the back pressure roller 43 as shown by arrow d by the above-mentioned up-down front-back moving mechanism, and the pressure head 45 is supported so that it can move back and forth freely along the axial direction of the back pressure roller 43 while maintaining a state of pressing the back pressure roller 43 downward with a prescribed force.

[0133] Use three Figure 6 The film polishing device shown, for example, is loaded with polishing film #600 in the first film polishing device, polishing film #400 in the second film polishing device, polishing film #1000 in the third film polishing device, and polishing film #2000 in the fourth film polishing device, to perform a piston rod polishing test.

[0134] It should be noted that the grinding conditions are the same as the grinding conditions for sample 1 shown in FIG. 28 of International Publication No. 2021 / 193107. During grinding, the rotation speed of the driving rollers 41 and 42 is set to 1400 rpm, and the pressing force of the pressure head 45 is set to 0.15-0.3 MPa. The steel rod used in the test has a diameter of 22 mm and a length of 200 mm.

[0135] When the above-mentioned grinding process is performed, as an example, for example, the following examples and comparative examples are generated. Fig.10 The samples with grinding marks in the brittle mode shown in (A) and (B) or the samples with grinding marks in the brittle mode shown in (A) and (B) Fig.11 (A) and (B) are samples with grinding marks in the ductile mode.

[0136] Fig.10 The grinding marks shown in (A) and (B) are as follows Fig.10 The enlarged photograph of (B) clearly shows a sample having a polishing mark in a brittle mode indicating a peeling mark caused by brittle fracture.

[0137] Fig.11 The grinding marks shown in (A) and (B) are as follows Fig.11 The enlarged photograph of (B) shows a sample having polishing marks in a ductile mode without peeling marks.

[0138] In the production Fig.10 The electroplated coating with grinding marks shown in (A) and (B) is used for Figure 1~Figure 4 When the piston rod 21 is electroplated, Figure 5 In the step S7 shown, grinding marks of a brittle mode showing peeling marks are generated on the surface by outer diameter grinding, and the surface cannot be finished to a desired surface roughness.

[0139] Figure 6 The film grinding device 40 shown is a device for finishing the outer peripheral surface of the piston rod, and is an important grinding device for finishing the outer peripheral surface of the piston rod to a desired surface roughness. During the outer diameter grinding, if the grinding marks of the above-mentioned brittle mode are generated, it will have a negative impact on the finishing accuracy of the outer peripheral surface of the piston rod, and excellent sliding characteristics, wear resistance and corrosion resistance cannot be obtained.

[0140] Therefore, as the electroplated film provided on the piston rod 21 applicable in the present embodiment, in the sample subjected to the above-mentioned grinding test, the grinding marks on the surface are observed, for example, by a microscope at a magnification of 200 times. Moreover, it is preferred to measure the number and width of the grinding marks in the same field of view, measure the number of grinding marks with a width of 8 μm or more, evaluate the quality of the electroplated film based on the number of generated grinding marks, and apply the selected electroplated film on this basis.

[0141] The reason why the grinding marks with a width of 8 μm or more were used as the criterion is that in the examples described below, when grinding tests were performed on a plurality of samples, the grinding marks in the brittle mode that produced peeling marks were mainly 8 μm or more in width.

[0142] According to the results of the embodiments described below, it is preferred to use a chromium electroplated coating that contains, in addition to chromium, one or more impurity elements selected from carbon and oxygen, and that contains 60 to 80 at% chromium and 16.5 to 30 at% carbon, and has an outer surface indentation hardness of more than 7 GPa.

[0143] The chromium electroplating film can be formed by using a strongly acidic electroplating bath containing the trivalent chromium salt, carboxylate, pH buffer and conductive salt at a pH of 0.1 to 0.6, a bath temperature of 55 to 80° C., and a cathode current density of 45 to 100 A / dm 2 Obtained by electroplating under conditions.

[0144] The plating film formed on the outer peripheral surface of the piston rod 21 under the above conditions has a coating hardness of 7 GPa or more. Figure 6 In the film polishing apparatus 40 shown, even when the outer diameter is polished under the above-mentioned conditions, it is difficult to generate a peeling mark (fracture mark in a brittle mode).

[0145] In addition, the above-mentioned electroplated film containing chromium: 60~80at% and carbon: 16.5~30at% can be used even if Figure 6 In the film polishing apparatus 40 shown, even when outer diameter polishing is performed under the above-mentioned conditions, peeling marks are unlikely to occur.

[0146] Therefore, even if the above-mentioned grinding process is performed, the piston rod 21 without peeling marks can be obtained.

[0147] However, in the aforementioned embodiment, the electroplated component in which the electroplated coating is formed by precipitating a trivalent chromium bath relative to the piston rod 21 is described, but the electroplated coating can be applied to automobile parts such as piston rings and brake pistons, and can also be applied to the sliding surfaces of various sliding parts such as the shafts of hydraulic machines and the gravure rollers of printing machines.

[0148] Example

[0149] A plurality of steel bars (22 mm in diameter, 200 mm in length) made of low carbon steel were prepared as test materials, and a strongly acidic plating bath (hereinafter simply referred to as A1) to which chromium chloride, glycine, boric acid, and ammonium chloride were added was used as a trivalent chromium plating bath.

[0150] In the case of A1 bath, at bath temperature 65~75℃, current density: 50~90A / dm 2、 The electroplating treatment was carried out under the condition of pH: 0.3~0.46, and a chromium electroplating film with a thickness of about 20μm was formed on the surface of the test material.

[0151] When a chromium plating bath (hereinafter referred to as A2) composed of weakly acidic blue chromium (trade name of Atotech Co., Ltd.) is used as a trivalent chromium plating bath, the bath temperature is 48 to 60°C and the current density is 40 to 90 A / dm 2、 The electroplating treatment was carried out under the condition of pH: 5.39~5.65, and a chromium electroplating film with a thickness of about 20μm was formed on the surface of the test material.

[0152] Figure 7 After the formation Fig. 9In the electroplated films of Examples 1 to 6 and Comparative Examples 1 to 12 shown, when the current density was adjusted to form each electroplated film at various deposition rates (film formation rates), the crystallinity (%) of each electroplated film was obtained based on the above formula (1). Since only halo patterns were observed in the range of 2θ: 30 to 60° in the XRD (X-ray diffraction) analysis results at any deposition rate, it was found that the electroplated film that remained as formed was an amorphous film with a crystallinity of 0.0%.

[0153] Figure 8A to Figure 8C After indicating Fig. 9 The component analysis results of each plated film of Examples 1 to 6 and Comparative Examples 1 to 12 are shown. The component analysis was performed using an electron probe microanalyzer under the conditions of an accelerating voltage of 10 kV and an irradiation current of 100 nA.

[0154] Can confirm, if Fig. 8A As shown in FIG. 1 , the electroplated films deposited by a trivalent chromium bath formed at various film forming speeds contain carbon as an impurity element. Figure 8B As shown, containing oxygen, such as Figure 8C As shown, it contains about 80at% chromium.

[0155] Fig. 9 Indicates the coating composition. Among the coating compositions of Examples 1 to 6, carbon, which has the highest content among the impurity elements, contains about 18 to 23 at%, and oxygen, which has the second highest content, contains about 1.5 to 5 at%. Specifically, carbon contains 18.1 to 22.8 at%, and oxygen contains 1.7 to 4.6 at%.

[0156] According to Figure 8, Fig. 9 , the carbon content can be adjusted by adjusting the deposition rate (film formation rate) of the electroplated film. It should be noted that the deposition rate can be selected under conditions of about 0.2 to 4 μm / min, or faster conditions, and can be adjusted according to the amount of chromium chloride added to the chromium electroplating bath. Therefore, it can be recognized that the carbon content can be adjusted within the range of 8 to 30 at% by adjusting the electroplating conditions.

[0157] The indentation hardness of the plated films was measured, and the results of component analysis of the samples after the hardness measurement were as follows: Fig. 9 The indentation hardness is the value measured by the instrumented indentation hardness using the nanoindentation method (ISO14577). The indentation weight is 20 mN.

[0158] exist Fig. 9In the embodiment, the samples with an outer surface indentation hardness of 7.5 GPa or more and a carbon content of 16.5 at% or more are recorded as examples, and the samples that do not meet the above conditions are recorded as comparative examples. In addition, the bath type of the sample manufactured using a strongly acidic electroplating bath is recorded as A1, and the bath type of the sample manufactured using a weakly acidic electroplating bath is recorded as A2. These electroplated films are all amorphous films in the XRD analysis results, so the crystallinity is shown as 0.0%.

[0159] Fig. 9 The samples of Examples 1 to 6 shown in the figure have an indentation hardness of 7.5 GPa or more. When the grinding test described below is performed, it can be determined that the grinding marks are in the ductile mode. Fig. 9 The grinding mark mode is recorded as ductile mode.

[0160] Fig. 9 The samples of Comparative Examples 1 to 12 shown in the figure have a hardness of less than 16 GPa or a carbon content of more than 16.5 to 30 at%. When the grinding test described below is performed, it can be determined that the grinding marks are in a brittle mode. Fig. 9 It is recorded as brittle mode in the grinding scar mode column.

[0161] "Grinding Test"

[0162] Use four Figure 6 The film polishing apparatus shown was loaded with a #600 polishing film in the first film polishing apparatus, a #400 polishing film in the second film polishing apparatus, and a #2000 polishing film in the third film polishing apparatus, and a piston rod polishing test was performed.

[0163] It should be noted that the grinding conditions are the same as those for the sample 2 shown in FIG. 28 of International Publication No. 2021 / 193107. The rotation speed of the driving rollers 41 and 42 during grinding is set to 1400 rpm, and the pressing force of the pressure head 45 is set to 0.15 to 0.3 MPa.

[0164] After the grinding test, the surface of the piston rod of Comparative Example 1 was magnified 500 times by a scanning electron microscope and the image was taken as follows: Fig.10 (A) shows an image taken at 5000 times magnification. Fig.10 (B) shown.

[0165] After the grinding test, the surface of the piston rod of Example 1 was magnified 500 times by a scanning electron microscope and the image was taken as follows: Fig.11 (A) shows an image taken at 5000 times magnification. Fig.11 (B) It can be confirmed that Fig.10 of Fig.11The vertical stripes in the up-and-down direction show traces of polishing the polishing film along the direction of the vertical stripes.

[0166] The sample of Comparative Example 1 is as follows Fig.10 (B) shows an enlarged view of a polishing mark (peeling mark) which is considered to be peeling failure caused by brittle fracture and is generated along the moving direction of the polishing film.

[0167] In contrast, the sample of Example 1 is Fig.11 As shown in an enlarged manner in (B), a polishing mark in the form of a flow is generated along the moving direction of the polishing film due to shear deformation.

[0168] The number and width of the friction marks existing in the field of view of 200 times magnification were observed at three locations of the piston rods of the examples and comparative examples using an optical microscope.

[0169] As a result, in all comparative samples, multiple polishing marks with a width of 8 μm or more were observed, and peeling failure was observed in the polishing marks with a width of 8 μm or more. In addition, in the example samples, no polishing marks that caused peeling were observed.

[0170] Based on the above results, when the plated film is subjected to the above polishing test, the number of polishing marks with a width of 8 μm or more is counted, which serves as a criterion for determining whether the plated film is in a brittle mode or a ductile mode in the above polishing test.

[0171] Fig.12 The results of measuring the coating hardness (GPa) and the number of polishing marks (marks / mm) having a width of 8 μm or more for the samples of Examples 1 to 6 and Comparative Examples 1 to 12 are shown.

[0172] Fig.13 The results of measuring the carbon content (at %) in the coating and the number of polishing marks (marks / mm) having a width of 8 μm or more for the samples of Examples 1 to 6 and Comparative Examples 1 to 12 are shown.

[0173] Fig.14 Indicates based on Fig.12 , Fig.13 The results shown are the correlation between the coating hardness and the carbon content in the coating.

[0174] like Fig.12 As shown, it can be seen that the occurrence of brittle mode polishing marks decreases above 7.5 GPa, with the film hardness being around 7.5 GPa as the boundary. On the other hand, only brittle mode polishing marks occur in the range of 5 to 7 GPa.

[0175] like Fig.13As shown, it can be seen that no brittle mode polishing marks are generated with the carbon content near 16.5 at % as the boundary. On the other hand, slight brittle mode polishing marks and brittle mode polishing marks are generated in the range of less than 16 at %.

[0176] Given these results, Fig.14 As shown in the figure, when the piston rod is ground by the above-mentioned grinding test, it is preferred that the electroplated film contains 16.5 at% or more carbon and has an outer surface indentation hardness of 7 GPa or more. These electroplated films can be judged as electroplated films precipitated by a trivalent chromium bath with no peeling marks as the center, with the grinding marks in the ductile mode.

[0177] It should be noted that, depending on the amount of organic components added to the electroplating bath, the effective carbon content of the electroplated film is 16.5 to 30 at%, considering that the limit of the carbon content of the electroplated film is about 30 at%. With this range of carbon content, the hardness of the electroplated film can be obtained. Fig.14 The hardness ranges from 7 to 15 GPa.

[0178] On the other hand, in the range of 6.0 to 6.9 GPa of electroplated coating hardness and 10 to 16 at% of carbon content, grinding marks of the brittle mode described above are generated. Furthermore, in the range of 6.9 GPa or more of coating hardness and less than 15 at% of carbon content, the transition mode before the change to the brittle mode or the ductile mode is shown. With respect to the change in each range, a different coating of chromium carbide is formed, and therefore, the coating hardness and carbon content shown in each range change.

[0179] These results show that the coating properties are affected by organic components such as carboxylates, pH buffers, and conductive salts in the electroplating bath. Furthermore, the amount of organic components contained in the coating also changes depending on the pH, bath temperature, and current density during electroplating.

[0180] Fig.15 (A) shows the analysis results of X-ray diffraction of the sample of Comparative Example 1, Fig.15 (B) is a surface photograph showing the polishing marks of the sample at 200 times magnification. Fig.15 In the surface photograph shown in (B), three polishing marks (accompanied by peeling failure) with a width of 8 μm or more can be confirmed as indicated in front of the arrows.

[0181] Fig.16 (A) shows the analysis results of X-ray diffraction of the sample of Example 1, Fig.16 (B) is a surface photograph showing the polishing marks of the sample.

[0182] according to Fig.15The X-ray diffraction analysis results shown in (A) show that the sample of Comparative Example 1 is a sample of 100% amorphous (0.0% crystallinity) showing only halo lines. Fig.16 The X-ray diffraction analysis results shown in (A) show that the sample of Example 1 is a sample of 100% amorphous (crystallization degree 0.0%) showing only halo lines. This sample has a carbon content of 22.8 at%, which is more than 16.5%, and a hardness of 12.7 GPa, which is more than 7 GPa, so it is in the ductile mode.

[0183] According to the above formula (1), the degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100%. The integrated intensity ratio of formula (1) is Fig.16 In (A), 2θ: 30-60°, half-value width of crystalline: <3, half-value width of amorphous: ≥3 are obtained.

[0184] according to Fig.16 According to the analysis results of X-ray diffraction shown in (A), the degree of crystallinity calculated based on formula (1) was 0.0%.

[0185] Fig.16 In the sample shown in (B), Fig.15 The width of the polishing marks in the structure shown in (B) is reduced. Therefore, it can be seen that even an amorphous sample with a crystallinity of 0.0% can reduce brittle polishing marks.

[0186] As before Fig. 9 As shown, in Examples 1 to 6, in the electroplated film having a composition of 72 to 80 at % chromium, 19 to 23 at % carbon, and 1.7 to 4.6 at % oxygen, by setting the hardness to 7.5 to 12.7 GPa, a ductile mode electroplated film can be obtained.

[0187] Fig.17 This is a graph showing the relationship between the deposition rate (film formation rate) and the orientation and the chromium crystal grain size of the electroplated films of Examples 2 and 5 and Comparative Examples 1, 4, 9, and 12.

[0188] according to Fig.17 , it can be seen that the chromium grains in the ductile mode coating are smaller than 10 nm. In addition, it can be seen that as the precipitation rate increases, the chromium grain size increases. The grain size shown here is the value of at least one side of each particle.

[0189] Fig.18 The TEM image of the cross section of the electroplated film of Example 2 in the ductile mode is shown. Fig.18 , the presence of chromium grains cannot be confirmed.

[0190] The structure of the plating film was observed using a transmission electron microscope (STEM) at an accelerating voltage of 200 kV.

[0191] Fig.19 TEM images of the cross section of the coating in the brittle mode are shown for Comparative Examples 1 and 4 using the bath seed A1. In both Comparative Examples 1 and 4, the presence of chromium crystal grains can be confirmed.

[0192] Fig. 20 The TEM image of the cross section of the coating in the ductile mode is shown for Example 5 using the bath seed A2. Fig. 20 The presence of chromium grains could not be confirmed.

[0193] Fig.21 TEM images of the cross section of the coating in the brittle mode are shown for Comparative Examples 9 and 12 using the bath seed A2. In both Comparative Examples 9 and 12, the presence of chromium crystal grains can be confirmed.

[0194] Fig. 22 The electron diffraction pattern of the film cross section in the ductile mode is shown for Example 2 using the bath seed A1. The measurement conditions for obtaining the electron diffraction pattern are an acceleration voltage of 200 kV, a wavelength λ of the electron beam at 200 kV of 0.00251 nm, and a camera length of 399.4 mm.

[0195] according to Fig. 22 , the first ring can be confirmed at the position of d value (distance between crystal planes) 2.0~2.3Å. This indicates that there are no oriented microcrystals, that is, chromium as the matrix (d value of chromium: 2.04Å). On the other hand, since no diffraction spots indicating crystallinity can be confirmed on the first ring, it is possible that no chromium crystal grains are contained.

[0196] Fig.23 The comparative example 1 ( Fig.23 (A)), Comparative Example 4 ( Fig.23 (B) ), Electron diffraction pattern of the film cross section in brittle mode.

[0197] according to Fig.23 In either (A) or (B), the first ring can be confirmed at a position with a d value (distance between crystal planes) of 2.0 to 2.3 Å. This indicates that non-oriented microcrystals, i.e., chromium, exist as a matrix (d value of chromium: 2.04 Å). On the other hand, since diffraction spots indicating crystallinity can be confirmed on the first ring, it is known that oriented chromium grains exist.

[0198] Fig.24The electron diffraction pattern of the film cross section in the ductile mode is shown for Example 5 using the bath seed A2.

[0199] according to Fig.24 , it can be confirmed that the first ring exists at a position with a d value (distance between crystal planes) of 2.0 to 2.3 Å. This indicates that non-oriented microcrystals, namely chromium, exist as a base material (d value of chromium: 2.04 Å). On the other hand, since no diffraction spots indicating crystallinity can be confirmed on the first ring, it is considered that there is a possibility that no chromium crystal grains are contained.

[0200] Fig.25 The comparative example 9 ( Fig.25 (A)), Comparative Example 12 ( Fig.25 (B) ), Electron diffraction pattern of the film cross section in brittle mode.

[0201] according to Fig.25 In either (A) or (B), the first ring can be confirmed to exist at a position with a d value (distance between crystal planes) of 2.0 to 2.3 Å. This indicates that non-oriented microcrystals, i.e., chromium, exist as a base material (d value of chromium: 2.04 Å). On the other hand, since diffraction spots indicating crystallinity can be confirmed on the first ring, it is known that oriented chromium crystal grains exist.

[0202] Description of Reference Numerals

[0203] 1…Shock absorber (cylinder device)

[0204] 2…Inner tube (cylinder)

[0205] 3…outer cylinder

[0206] 15…Oil seal

[0207] 21…Piston rod

[0208] 25…Piston

[0209] A…Sliding range

Claims

1. A plated component having, on its outer surface, an electroplated film containing at least chromium, carbon, and oxygen, with chromium precipitated from a trivalent chromium bath as a main component, wherein the electroplated film contains chromium: 60 to 80 at%, carbon: 16.5 to 30 at%, and the indentation hardness of the outer surface is 7 GPa or more, The peak integrated intensity ratio of the measured value of the X-ray diffraction measurement and the crystallinity calculated by the following formula (1) is 4% or less, Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1) in, The indentation hardness is a value measured by instrumented indentation hardness using a nanoindentation method (ISO14577), and the integrated intensity ratio of formula (1) is a value obtained in XRD (X-ray diffraction) analysis with 2θ: 30-60°, half-value width of crystalline: <3, and half-value width of amorphous: ≥3.

2. The electroplated component according to claim 1, In the film inspection using electron beam diffraction, the electroplated film has no diffraction spots at positions where the inter-plane distance d value is 2.0 to 2.0 Å.

3. The electroplated component according to claim 1 or claim 2, The plated part is a sliding contact part that is in sliding contact with the sliding part.

4. The electroplated component according to claim 1 or claim 2, The oxygen concentration of the electroplated film is 2-6 at %.

5. A method for manufacturing an electroplated component, which is a method for manufacturing an electroplated component having an electroplated coating, wherein the electroplated coating is formed by electroplating with chromium precipitated in a trivalent chromium bath as a main component, the method for manufacturing an electroplated component comprising an electroplating step of forming an electroplated coating composed of a hard layer composed of chromium precipitated in a trivalent chromium bath as a main component on the surface of the electroplated component, the electroplating step being carried out in an electroplating bath containing a trivalent chromium salt, a carboxylate, a pH buffer material and a conductive salt, at a bath temperature of 55 to 80° C., at a cathode current density of 45 to 100 A / dm 2 The electroplating film is formed under the conditions of.

6. The method for manufacturing a plated component according to claim 5, The electroplated film is an electroplated film containing at least chromium, carbon, and oxygen, and having chromium precipitated from a trivalent chromium bath as a main component, the electroplated film containing chromium: 60-80at%, carbon: 16.5-30at%, and an outer surface indentation hardness of 7GPa or more. in, The indentation hardness refers to a value measured by instrumented indentation hardness using a nanoindentation method (ISO 14577).

7. The method for manufacturing a plated component according to claim 5 or claim 6, In the film inspection using electron beam diffraction, the electroplated film has no diffraction spots at positions where the inter-plane distance d value is 2.0 to 2.0 Å.

8. The method for manufacturing a plated component according to claim 5 or claim 6, The plated part is a sliding contact part that is in sliding contact with the sliding part.

9. The method for manufacturing a plated component according to claim 5 or claim 6, The oxygen concentration of the electroplated film is 2-6 at %.

10. The method for manufacturing a plated component according to claim 5 or claim 6, In the plated film, the peak integrated intensity ratio of the measured value of the X-ray diffraction measurement and the crystallinity calculated by the following formula (1) are 4% or less, Degree of crystallinity (peak integrated intensity ratio) = {(crystalline) / (crystalline+amorphous)} × 100% (1) in, The integrated intensity ratio of the above formula (1) indicates a value obtained in XRD (X-ray diffraction) analysis with 2θ: 30 to 60°, half value width of crystalline: <3, and half value width of amorphous: ≥3.

Citation Information

Patent Citations

  • Gravure plate making roll and its manufacturing method

    JP2008143169A